2016
DOI: 10.1016/j.juro.2016.01.010
|View full text |Cite
|
Sign up to set email alerts
|

A Parallel Randomized Clinical Trial Examining the Return of Urinary Continence after Robot-Assisted Radical Prostatectomy with or without a Small Intestinal Submucosa Bladder Neck Sling

Abstract: PurposeUrinary continence is a driver of quality of life after radical prostatectomy. The purpose of this study was to evaluate the impact of a biologic bladder neck sling on postoperative return of urinary continence after robot-assisted radical prostatectomy (RARP). Materials and MethodsThis study compared early continence in patients undergoing RARP with a sling and without a sling in a two group, 1:1, parallel, randomized controlled trial. Patients were blinded to group assignment. The primary outcome was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 16 publications
1
19
0
Order By: Relevance
“…95%CI: −0.54 to 3.13) (Figure 3). Study by Bahler et al was not included in this meta-analysis as the study did not report confidence interval for the data, however, the study coincides with our finding 18 (n = 104) (MD: −0.4; p = 0.61; 95% CI: not reported).…”
Section: Continence Outcomessupporting
confidence: 68%
See 2 more Smart Citations
“…95%CI: −0.54 to 3.13) (Figure 3). Study by Bahler et al was not included in this meta-analysis as the study did not report confidence interval for the data, however, the study coincides with our finding 18 (n = 104) (MD: −0.4; p = 0.61; 95% CI: not reported).…”
Section: Continence Outcomessupporting
confidence: 68%
“…10,[18][19][20][22][23][24] However, with continence definition of ≤ 1pad/day, there was a low to moderate-quality evidence that sling procedures did not reduce the risk of incontinence at 1 month (RR:1.12; 95%CI: 1.00 to 1.24), 3 months (RR:1.07; 95%CI: 0.95 to 1.21), 6 months (RR:1.01; 95%CI: 0.95 to 1.07), and 12 months (RR: 1.02; 95%CI: 0.93 to 1.13) postoperatively (n = 794) (Figure 2). 10,18,22,24,26 Sling procedure did not reduce the time taken to achieve continence with zero pad/day definition 20,25 (n = 296) (MD: 1.29;…”
Section: Continence Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…The main limitations of all the above studies have been related to small numbers and nonrandomization to a control group. Subsequently, Bahler et al failed to show any benefit of using SIS sling at the time of RP on continence status compared with controls at 1‐month follow‐up in a randomized controlled trial. In this study, zero pad status was observed in 13 of 67 in the sling group vs 13 of 68 in the control group.…”
Section: Peroperative Measures In the Prevention Of Uimentioning
confidence: 99%
“…Reference Technique Preservation Friedlander 18 Bladder neck sparing Lim 30 Retzius sparing Reinforcement Lee 24 Bladder neck plication stitch Bahler 22 Small intestinal submucosa bladder neck sling Lei 19 Selective suture ligation of dorsal venous complex Patel 20 Periurethral suspension stitch Nguyen 21 Urethral sling fashioned from autologous vas deferens Dal Moro 27 Complete Reconstruction of the Posterior Urethral Support (CORPUS) Reconstruction Propiglia 23 Total anatomical reconstruction Student 25 Advanced reconstruction of vesicourethral support (ARVUS) Jeong 26 1-step posterior reconstruction Hurtes 28 Anterior retropubic suspension with posterior reconstruction Coelho 29 Modified posterior reconstruction showing that the procedure is effective in long term cancer control, even in patients with high-risk disease (Table 2). 43e49 Theoretically, robot-assisted surgery should be the ideal model to determine the impact and limitations of "surgical precision" providing better ergonomic for the surgeon, particularly during reconstructive steps, better vision and magnification during dissection of the prostate and surrounding anatomical details.…”
Section: Anatomical Principlementioning
confidence: 99%